The development of a non-communicable disease prevention training program using youtube and its effect on community health volunteer's self-efficacy - Hamidun, Aliff Ridzwan (2022)
Background: Community education is one of the important public health interventions in curbing the rising concern of non-communicable disease (NCD) incidence and its complications. Community health volunteers (CHVs) were recruited to outreach the community by delivering information on NCD prevention. Training is essential to ensure effective and efficient education by the CHVs. Training through YouTube is an option to overcome the limitation of class-based training. Objective: To develop a YouTube-based training program and to determine the effect of the program on self-efficacy and task importance in NCD prevention education among CHVs in Kelantan. Methods: The self-efficacy (SE) and Task Importance Rating Scale of 14 CHV tasks were developed via nominal group technique (NGT) and validated toَ measureَ CHV’sَ SE and task importance. A training needs survey was conducted using the newly developed rating scale (n=78), and Importance-Performance Analysis was performed to identify CHV’sَ needsَ forَ trainingَ whichَ was used for the development of the module. NGT with expert and senior CHVs was also conducted. The module was evaluated using one arm before and after an interventional study among CHVs in Pasir Mas. Participants were given four weeks to watch 12 YouTube training videos. The self-efficacy (SE) and Task Importance Rating Scale was collected pre and postintervention to compare the mean SE and tasks Importance score before and after the intervention using RM MANOVA (n=35). Theَ analysisَ alsoَ includedَ CHV’sَ experience and highest education level as the independent variables. Fourteen models of RM MANOVA were developed for each task.